A phenotypic and genotypic characterisation of strain types, virulence factors and agr groups of colonising Staphylococcus aureus associated with bloodstream infection - Karayem, Karayem (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015